Oxidation Processes in Blowing Steel With Inert Gas into the Ladle; IOP Conference Series: Materials Science and Engineering; Vol. 91: VI International Scientific Practical Conference on Innovative Technologies and Economics in Engineering, Yurga, Russia, 21-23 May 2015 - Gizatulin R. A. Rinat Akramovich; Valuev D. V. Denis Viktorovich; Trifonov V. A. Vladimir Aleksandrovich; Valueva A. V. Anna Vladimirovna; Serikbol A. (Innovative technologies for producing and machining materials in mechanical engineering, 2015)
Title screen